2013
DOI: 10.1016/j.stemcr.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

LNGFR+THY-1+VCAM-1hi+ Cells Reveal Functionally Distinct Subpopulations in Mesenchymal Stem Cells

Abstract: SummaryHuman mesenchymal stem cells (hMSCs), which conventionally are isolated based on their adherence to plastic, are heterogeneous and have poor growth and differentiation, limiting our ability to investigate their intrinsic characteristics. We report an improved prospective clonal isolation technique and reveal that the combination of three cell-surface markers (LNGFR, THY-1, and VCAM-1) allows for the selection of highly enriched clonogenic cells (one out of three isolated cells). Clonal characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
206
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(223 citation statements)
references
References 50 publications
5
206
0
3
Order By: Relevance
“…Moreover, uncultured CD271+Thy1+ were detected in the BM of immunocompromised mice upon transplantation and retained their colony formation and trilineage differentiation ability in vitro (Mabuchi et al, 2013). Other combinations such as CD146 and CD105 (Isern et al, 2013) or Integrin aV and PDGF Receptor a (PDGFRa) (also known as CD51 and CD140a, respectively) have been demonstrated to highly enrich for clonogenic cells in the human BM, as demonstrated by sphere formation assay and the ability to support primitive hematopoietic cells in vitro.…”
Section: Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, uncultured CD271+Thy1+ were detected in the BM of immunocompromised mice upon transplantation and retained their colony formation and trilineage differentiation ability in vitro (Mabuchi et al, 2013). Other combinations such as CD146 and CD105 (Isern et al, 2013) or Integrin aV and PDGF Receptor a (PDGFRa) (also known as CD51 and CD140a, respectively) have been demonstrated to highly enrich for clonogenic cells in the human BM, as demonstrated by sphere formation assay and the ability to support primitive hematopoietic cells in vitro.…”
Section: Reviewmentioning
confidence: 95%
“…Focusing definitions on cell features in vitro has unfortunately not helped resolve features of the cell in vivo and may be misleading, since there is evidence of a marked global gene expression difference depending on whether the cells are freshly isolated or cultured (Churchman et al, 2012;Harichandan et al, 2013). The expression of cell surface molecules such as low-affinity nerve growth factor receptor (LNGFR), also known as CD271, and the melanoma cell adhesion molecule (MCAM), also known as CD146, both of which have been described to label uncultured multipotent MSCs (Mabuchi et al, 2013;Sacchetti et al, 2007;Tormin et al, 2011) are altered when the cells are cultured. In the case of CD271, its expression is lost when cultured in media containing bFGF (Quirici et al, 2002).…”
Section: Historical Backgroundmentioning
confidence: 99%
“…RECs exhibited robust multilineage differentiation and selfrenewal potency, and were therefore considered to be the most primitive and undifferentiated population. 49 Last, in addition to CD146 and THY-1, other markers, such as MSCA-1 and SUSD2, have also been used to isolate subpopulations of MSCs, 50 and furthermore, differences in differentiation potential of single-sorted BMSC-derived CFU-Fs point to a possible hierarchical structure of the primary MSC compartment. 15 Here, our current ongoing single-cell gene expression experiments will hopefully contribute to further clarify this important aspect of primary MSC biology.…”
Section: But Not In the Cd271mentioning
confidence: 99%
“…These cells differentiate into bone and fat on ectopic transplantation in vivo. In 2013, our group reported that the LNGFR and THY-1 double-positive population (i.e., the LT population) have a high CFU-F frequency in the BM [8]. CFU-F can be classified into three different cell groups based on proliferation ability.…”
Section: Prospective Identification and Isolation Of Human Mscsmentioning
confidence: 99%
“…MSCs reside in the non-hematopoietic fraction and can be cultured to form fibroblast-like colonies (colony-forming unit fibroblasts: CFU-Fs) in vitro [4][5][6][7]. MSCs are found in the BM [8,9], umbilical cord blood [10,11], placenta [12,13], dental pulp [14,15], adipose tissue [16][17][18][19], and synovium [20][21][22]. BM-MSCs are thought to function in the maintenance of BM homeostasis, restoration of injured bone, and regulation of differentiation in HSCs [23].…”
Section: Introductionmentioning
confidence: 99%